2012
DOI: 10.1371/journal.pone.0030301
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization Strategies for Unstable Dynamics

Abstract: BackgroundWhen humans are faced with an unstable task, two different stabilization mechanisms are possible: a high-stiffness strategy, based on the inherent elastic properties of muscles/tools/manipulated objects, or a low-stiffness strategy, based on an explicit positional feedback mechanism. Specific constraints related to the dynamics of the task and/or the neuromuscular system often force people to adopt one of these two strategies.Methodology/FindingsThis experiment was designed such that subjects could a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…As shown by Saha and Morasso (2012) the shape and size of the stiffness ellipse depend on the relative position of the two hands and the virtual mass. The major axis of the ellipse is approximately aligned with the line linking the two hands and the ratio between the major and the minor axis grows with an increasing separation of the two spring terminals.…”
Section: Strategy Switching In the Stabilization Of The Inverted Pendmentioning
confidence: 96%
See 3 more Smart Citations
“…As shown by Saha and Morasso (2012) the shape and size of the stiffness ellipse depend on the relative position of the two hands and the virtual mass. The major axis of the ellipse is approximately aligned with the line linking the two hands and the ratio between the major and the minor axis grows with an increasing separation of the two spring terminals.…”
Section: Strategy Switching In the Stabilization Of The Inverted Pendmentioning
confidence: 96%
“…A novel approach (Saha and Morasso, 2012;Zenzeri et al, 2014) was conceived with the aim to put the participants in an experimental situation that was as neutral as possible with the respect to the choice of the strategy: in this approach, individuals are trained to use a virtual tool (VUBT: Virtual Underactuated Bimanual Tool), with a tool-tip under the action of a saddle-like force field, and the studies investigated two main questions, namely which strategy do naïve people prefer and how difficult is it to switch from one strategy and the other for expert users?…”
Section: Strategy Switching In the Stabilization Of The Inverted Pendmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, this task forces the subject to finely tune his motor output in response to force perturbations to contrast the instability. We have previously demonstrated that, despite the task being very challenging for a naïve user, it supports the learning of two specific different patterns of bimanual coordination that solve the balancing problem [11], [12]: a high stiffness feedforward strategy and a low stiffness positional feedback strategy. In this work, we analyze how these two patterns accommodate in the case of a dyadic configuration and test whether it allows for performance advantages compared to a bimanual scheme.…”
mentioning
confidence: 93%